Can urban green infrastructure influence the urban heat island effect and air quality nexus? - Ralph Fares; Stephen Matheson; Jua Cilliers; Sebastian Pfautsch; Fraser R. Torpy; Peter J. Irga (Environmental Pollution, 2026)

A numerical assessment of microclimate and cooling effects of a modular street parklet for urban heat mitigation - Qingyun Wu; Peter Irga; Lehan Chen; Christof Gromke; Fraser R. Torpy; Gabrielle Duani; Ralph Fares; Sebastian Pfautsch; Chengwang Lei; Yuhan Huang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Cooling under pressure: The capacity of the urban forest to reduce air temperature during extreme heat - Sinéad Nicholson; Negin Nazarian; Pui Kwan Cheung; Stephen J. Livesley; Sebastian Pfautsch (Urban Forestry & Urban Greening, 2026)

A battleground of climate change: Summer air temperatures in social housing - Sebastian Pfautsch; Agnieszka Wujeska-Klause; Judi R. Walters; Abby Mellick Lopes; Louise Crabtree-Hayes; Emma Power; Bhavya Chitranshi; Helen Armstrong; Katherine Gibson; Cameron Tonkinwise; Stephen Healy (Urban Climate, 2026)

The heat-safe play index (H-SPI): A tool to compare relative thermal safety of outdoor playgrounds - Judi R. Walters; Sebastian Pfautsch (Urban Forestry & Urban Greening, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Tree crown traits and planting context contribute to reducing urban heat - Mahmuda Sharmin; Mark G. Tjoelker; Sebastian Pfautsch; Manuel Esperon-Rodriguez; Paul D. Rymer; Sally A. Power (Urban Forestry & Urban Greening, 2023)

Measuring local-scale canopy-layer air temperatures in the built environment: A flexible method for urban heat studies - Sebastian Pfautsch; Agnieszka Wujeska-Klause; Judi R. Walters (Computers, Environment and Urban Systems, 2023)

The temperature optima for tree seedling photosynthesis and growth depend on water inputs - Dushan P. Kumarathunge; John E. Drake; Mark G. Tjoelker; Rosana López; Sebastian Pfautsch; Angelica Vårhammar; Belinda E. Medlyn (Global Change Biology, 2020)
Understanding how tree growth is affected by rising temperature is a key to predicting the fate of forests in future warmer climates. Increasing temperature has direct effects on plant physiology, but there are also indirect effects of increased water limitation because evaporative demand increases with temperature in many systems. In this study, we experimentally resolved the direct and indirect effects of temperature on the response of growth and photosynthesis of the widely distributed species Eucalyptus tereticornis . We grew E. tereticornis in an array of six growth temperatures from 18 to 35.5°C, spanning the climatic distribution of the species, with two watering treatments: (a) water inputs increasing with temperature to match plant demand at all temperatures ( W incr ), isolating the direct effect of temperature; and (b) water inputs constant for all temperatures, matching demand for coolest grown plants ( W const ), such that water limitation increased with growth temperature. We found that constant water inputs resulted in a reduction of temperature optima for both photosynthesis and growth by ~3°C compared to increasing water inputs. Water limitation particularly reduced the total amount of leaf area displayed at T opt and intermediate growth temperatures. The reduction in photosynthesis could be attributed to lower leaf water potential and consequent stomatal closure. The reduction in growth was a result of decreased photosynthesis, reduced total leaf area display and a reduction in specific leaf area. Water availability had no effect on the response of stem and root respiration to warming, but we observed lower leaf respiration rates under constant water inputs compared to increasing water inputs at higher growth temperatures. Overall, this study demonstrates that the indirect effect of increasing water limitation strongly modifies the potential response of tree growth to rising global temperatures.

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.

Hydraulic Anatomy and Function of Trees—Basics and Critical Developments - Sebastian Pfautsch (Current Forestry Reports, 2016)

Vessel diameter and related hydraulic traits of 31 Eucalyptus species arrayed along a gradient of water availability - Sebastian Pfautsch; Craig Macfarlane; Marco Harbusch; Anita Wesolowski; Renee Smith; Matthias Boer; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology, 2016)
We present two comprehensive data sets that describe xylem vessel diameters and related sapwood traits for species of Eucalyptus from arid and semi‐arid woodlands and forests in Australia. Between 2009 and 2014, sapwood of mature trees was sampled in south‐western, south‐eastern and eastern Australia. One additional species was sampled from tropical north‐western Australia. The first data set describes samples collected from the basal stem section (130 cm above ground) of three individuals of 31 species of which eight species were replicated at sites that differed in climatic conditions. The second data set describes vessel characteristics of three trees from each of 10 species that were sampled at 8 m below the tree apex. The sampled trees of these 10 species are also part of the first data set. In total, we report diameters (D) for over 25 100 vessels, from 494 digital images taken from 117 trees. We also report vessel frequencies, void‐to‐wood ratios, sapwood densities and hydraulically weighted vessel diameters (Dh). Supporting data of the first data set include tree diameter at breast height (130 cm above ground), tree height, sample locations, and summary climate data. In this data set, diameter of individual vessels ranges from 10 to over 300 μm, and vessel frequency from 360 to 9070 vessels cm −2 . Wood density ranges from 0.47 to 0.96 g cm −3 . Void‐to‐wood ratio ranges from 6% to 27% and Dh ranges from 46 to 236 μm. Mean annual rainfall (P) at sample sites ranges from 246 to 2274 mm and FAO 56 reference evaporation (E) from 777 to 2110 mm. The aridity index (E/P) ranges from 0.15 to 2.93 (dimensionless). Tree diameters range from 9 to 90 cm and tree heights range from 6 to 70 m. D and Dh in the second data set range from 11 to 271 and 68 to 205 μm, respectively. These datasets will make a valuable contribution to future continental‐scale and global‐scale studies of the relationship between xylem hydraulic architecture and climate. The data sets are unique in the sense that they are phylogenetically constrained, allowing in‐depth assessment of plasticity of hydraulic attributes within a single tree genus.

Climate determines vascular traits in the ecologically diverse genus Eucalyptus - Sebastian Pfautsch; Marco Harbusch; Anita Wesolowski; Renee Smith; Craig Macfarlane; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology Letters, 2016)
Current theory presumes that natural selection on vascular traits is controlled by a trade‐off between efficiency and safety of hydraulic architecture. Hence, traits linked to efficiency, such as vessel diameter, should show biogeographic patterns; but critical tests of these predictions are rare, largely owing to confounding effects of environment, tree size and phylogeny. Using wood sampled from a phylogenetically constrained set of 28 Eucalyptus species, collected from a wide gradient of aridity across Australia, we show that hydraulic architecture reflects adaptive radiation of this genus in response to variation in climate. With increasing aridity, vessel diameters narrow, their frequency increases with a distribution that becomes gradually positively skewed and sapwood density increases while the theoretical hydraulic conductivity declines. Differences in these hydraulic traits appear largely genotypic in origin rather than environmentally plastic. Data reported here reflect long‐term adaptation of hydraulic architecture to water availability. Rapidly changing climates, on the other hand, present significant challenges to the ability of eucalypts to adapt their vasculature.

Stomatal structure and physiology do not explain differences in water use among montane eucalypts - Mana Gharun; Tarryn L. Turnbull; Sebastian Pfautsch; Mark A. Adams (Oecologia, 2015)

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Relating water use to morphology and environment of Nothofagus from the world’s most southern forests - Sebastian Pfautsch; Pablo L. Peri; Craig Macfarlane; Floris van Ogtrop; Mark A. Adams (Trees, 2014)

Water flux of Eucalyptus regnans: defying summer drought and a record heatwave in 2009 - Sebastian Pfautsch; Mark A. Adams (Oecologia, 2013)

Assessing sapwood depth and wood properties in Eucalyptus and Corymbia spp. using visual methods and near infrared spectroscopy (NIR) - Sebastian Pfautsch; Craig Macfarlane; Nicholas Ebdon; Roger Meder (Trees, 2012)